Workshop Konsep Dasar Penelitian Tindakan Kelas bagi Guru - Ayuningrum, Syamzah; Herzamzam, Dyah Anungrat; Sintya, Hani; Aslamia, Arneta Shohibatul; Damayanti, Hanifah (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
This community service aims to increase teachers' understanding of creating and producing scientific work through Classroom Action Research (CAR). This research was carried out for 68 teachers throughout Indonesia. The implementation of this training is carried out online using the zoom meeting application and WhatsApp group. The details of the training materials are Basic Concepts, Procedures for implementing (CAR), and selection of Models, Strategies, and learning methods. The teachers seemed very enthusiastic even though the training was conducted using an online system. This can be seen from the active teachers asking questions during the question and answer session and telling stories about their experiences so far. It can be seen from the training that teachers have understood the implementation of (CAR) concerning (CAR) reports that have been made by the participants or teachers. It can be concluded that this training positively impacts teachers who can identify the basic concepts and procedures for implementing PTK and choosing learning models, strategies and methods.